Atomically distributed Al-F3 nanoparticles towards precisely modulating pore size of carbon membranes for gas separation - Xiuling Chen; Zhiguang Zhang; Shan Xu; Bin Zhang; Yong Qin; Canghai Ma; Gaohong He; Nanwen Li (Nature Communications)
Abstract To confront the energy consumption, high performance membrane materials are urgently needed. Carbon molecular sieve (CMS) membranes exhibit superior capability in separating gas mixtures efficiently. However, it remains a grand challenge to precisely tune the pore size and distribution of CMS membranes to further improve their molecular sieving properties. Herein, we report an approach of finely modulating CMS pore structure by using the reactive Al(CH3)3 to in situ defluorinate the polymer precursor to form Al-Fx(CH3)3-x in the polymer matrix, which is further converted to atomic-level Al2O3 and Al-F3 in the polymer matrix. These nanoparticles play the key role in regulating the pore size of CMS membranes by suppressing the formation of unfavorable large pores during pyrolysis, thus enhancing the gas selectivity considerably. The resultant CMS membranes demonstrate a H2/CH4 and CO2/CH4 selectivity of 192.6, and 58.4, respectively, 128% and 93% higher than the untreated samples, residing far above the latest upper bounds.